Polytene chromosomes reflect functional organization of the Drosophila genome - D. S. Sidorenko; T. Yu. Zykova; V. A. Khoroshko; G. V. Pokholkova; S. A. Demakov; J. Larsson; E. S. Belyaeva; I. F. Zhimulev (Вавиловский журнал генетики и селекции)
Polytene chromosomes of Drosophila melanogaster are a convenient model for studying interphase chromosomes of eukaryotes. They are giant in size in comparison with diploid cell chromosomes and have a pattern of cross stripes resulting from the ordered chromatid arrangement. Each region of polytene chromosomes has a unique banding pattern. Using the model of four chromatin types that reveals domains of varying compaction degrees, we were able to correlate the physical and cytological maps of some polytene chromosome regions and to show the main properties of genetic and molecular organization of bands and interbands, that we describe in this review. On the molecular map of the genome, the interbands correspond to decompacted aquamarine chromatin and 5’ ends of ubiquitously active genes. Gray bands contain lazurite and malachite chromatin, intermediate in the level of compaction, and, mainly, coding parts of genes. Dense black transcriptionally inactive bands are enriched in ruby chromatin. Localization of several dozens of interbands on the genome molecular map allowed us to study in detail their architecture according to the data of whole genome projects. The distribution of proteins and regulatory elements of the genome in the promoter regions of genes localized in the interbands shows that these parts of interbands are probably responsible for the formation of open chromatin that is visualized in polytene chromosomes as interbands. Thus, the permanent genetic activity of interbands and gray bands and the inactivity of genes in black bands are the basis of the universal banding pattern in the chromosomes of all Drosophila tissues. The smallest fourth chromosome of Drosophila with an atypical protein composition of chromatin is a special case.  Using the model of four chromatin states and fluorescent in situ hybridization, its cytological map was refined and the genomic coordinates of all bands and interbands were determined. It was shown that, in spite of the peculiarities of this chromosome, its band organization in general corresponds to the rest of the genome. Extremely long genes of different Drosophila chromosomes do not fit the common scheme, since they can occupy a series of alternating bands and interbands (up to nine chromosomal structures) formed by parts of these genes.